The Effect of Teachers' Professional and Pedagogical Competencies on Mathematics Learning Outcomes of Students at Madrasah Ibtidaiyah - Anggun Putri Yunanti; Aam Amaliyah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Competence is the ability or skill of an individual that is still in the form of potential. In the context of education, teacher competence, both professional and pedagogical, plays an important role in influencing student learning outcomes. Objective: This study aims to determine whether teachers' professional and pedagogical competencies influence students' mathematics learning outcomes at Madrasah Ibtidaiyah Negeri 02 Lebong. Method: The approach used in this study was ex post facto. This study was conducted in 2023 with a sample of 24 students. Data collection was carried out through questionnaires and documentation. Data analysis used normality tests, homogeneity tests, and paired t-tests. Results: The results showed that teachers' professional and pedagogical competencies had a significant effect on students' mathematics learning outcomes at Madrasah Ibtidaiyah Negeri 02 Lebong. Conclusion: Teachers' professional and pedagogical competencies play an important role in improving students' mathematics learning outcomes. Therefore, developing teachers' competencies in these two areas is very important for improving the quality of education at Madrasah Ibtidaiyah. Contribution: This study is expected to contribute scientifically to the field of education, particularly education at Madrasah Ibtidaiyah, by providing insight into the influence of teachers' professional and pedagogical competencies on student learning outcomes.